PENTINGNYA MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA SD NEGERI SEJATI - Pradita, Erni; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
Learning interest plays a significant role in determining the success of learning activities, especially at the elementary school level. One effective strategy to increase students' learning interest is through the use of interesting and appropriate learning media. This article aims to analyze the important role of learning media in fostering elementary school students' learning interest. The approach used in this study is qualitative, with data collection methods through interviews. Data were obtained from interviews with teachers and documents related to the learning process, and reinforced by literature reviews from various trusted sources such as scientific articles. The results of this study indicate that diverse learning media such as visual, audio-visual, and interactive technology can create a more enjoyable learning environment and support optimal understanding of the material. In addition, the media also plays a role in fostering curiosity and learning motivation in students. Therefore, teachers are expected to be able to utilize learning media creatively so that learning becomes more effective, interesting, and meaningful for students.